HUBUNGAN BEBAN TAS SEKOLAH DENGAN KEJADIAN FORWARD HEAD POSTURE PADA SISWA(I) SMA NEGERI 2 MAKASSAR - Rahdiah Idarwati; Yery Mustari, S.Ft., Physio., MClinRehab, CMTP; Immanuel Maulang, S.Ft., Physio., M.Kes, Sp.F.OR, AIFO, CMTP; Asdar Fajrin Multazam, S.Ft., Physio, M.Kes., CDNP, Dip.ASTR, CMTP (Indonesian Journal of Physiotherapy, 2026)
Background. FHP is a condition where the head shifts forward past the vertical line of the body. In recent years, the prevalence of musculoskeletal disorders in adolescents has increased, which is thought to be due to the use of school bags. Purpose To determine the relation between bag load and the incidence of FHP in students. Method. This study was conducted with a population of students in grades 10-12 who were measured for 5 school days. The determination of the sample of this study used the purposive sampling method and obtained a sample of 300 people. This study measured the burden of students' bags and measured CVA and TFL with the APECS application. Result. In this study, the results showed that the average weight of student's bags during a week was 2.07 kg. The weight of the bags carried by women tended to be heavier than men. In the CVA measurement when wearing a bag, there was an increase in students who experienced FHP. In the TFL measurement when wearing a bag, there was a variation and increase in the degree of TFL, compared to the neutral position. Conclusion. The weight of the bag and the incidence of FHP have a significant relation with the weak category. The comparison between the average body weight and the average weight of the bag carried by students in one week is categorized as normal. The prevalence of FHP measured in the neutral position was 33.3% and increased by 18.7% after wearing a bag Keywords: School Bag Weight; Craniovertebral Angle; Trunk Forward Lean; Forward Head Posture